Provision Impact Analysis of Motorcycle Exclusive Lanes on the Performance of Road Sections Using the Method MKJI 1997 and Vissim Software - Amar Mufhidin; Salma Karimah; Muhammad Isradi; Andri Irfan Rifai (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study aims to determine the performance of the road before and after the provision of motorcycle lanes. It also aims to determine the lane effect on vehicle speed and alternative solutions. Design/methodology/approach: In this study, MKJI 1997 and Vissim Software were used as the research methods. Findings: The results of the existing road performance showing that the vehicle speed, DS, and level of service were 38.66 km/h, 0.84, and D, respectively. This indicated that the provision of motorcycle lanes was effective in improving road performance, due to the level of service for the LV and HV lanes increasing from D to B, with a speed increasing from 36.99 km/h to 40.25 km/h. The results showed that the level of service for the motorcycle lane increased from D to C and the vehicle speed was 49.92 km/h. While the level of service for LV and HV lanes being consistent with B and the vehicle speed was 40,04 km/h. Research limitations/implications: The level of service for the motorcycle lanes decreased from D to F with the speed decreased from 46.13 km/h to 41.23 km/h, subsequently indicating that the alternative solution was to widen the motorcycle lane. Practical implications: Margonda Road is one of the congestion points in Depok City. Margonda Road connecting Depok and Jakarta. The composition of motorcycles on Margonda Road reach more than 80% of the traffic flow. This conditions has an impact on decrease the road performance. In this study, the provision of motorcycle lanes will be carried out using the Vissim Software simulation, where the application of lanes is considered to be the solution to this problem. Originality/value: This paper is original Paper type: a Research Paper